UiTM Sarawak ladies' staff volleyball team - Sim Phek Lin, Sandra (Universiti Teknologi MARA, Sarawak, 2016)
Recently, UiTM Sarawak ladies’ staff volleyball team, together with the golf, badminton, ping pong, veteran football, men’s Futsal, ladies’ Futsal, dart and sepak takraw teams, participated in the 4th Borneo Friendship Games among staff of higher institutions of learning. The competition was held from 1 9 to 22 April 2016 at Universiti Sabah Malaysia (UMS) in Sabah. The UiTM Sarawak ladies’ staff volleyball team comprised Dr. Sandra Sim Phek Lin (Team Manager and Captain), Muliyono Piang (coach) and nine players (Rasmini bt. Kasmin, Asfalaila bt. Ibrahim, Zainon bt. Hj. Bibi, Hartini bt. Mahidin, Napsiah bt. Putit, Suhaida bt. Halamy, Aima Sumiyati bt. Maliki, Kadariah bt. Hj. Yassin and Jong Li Ling. The team trained daily for three months in preparation for the tournament. Their enthusiasm, high fighting spirit (with UiTM Sarawak’s motto: Focus, Guarantee, Bo/eh, Yes! Yes! Yes!) and determination bore fruit as they emerged as the first runner-up after beating UNIMAS with a score of 2:1 and Politeknik Kota Kinabalu (PKK) with a score of 2:0. All the players gained a lot of experience during this tournament, especially when playing against UMS which emerged as the champion.